PERBEDAAN WAKTU REAKSI PADA USIA LANJUT DENGAN HIPOTENSI ORTOSTATIK DAN TANPA HIPOTENSI ORTOSTATIK - Nurullita, Tika; Fakhrurazzy, Fakhrurazzy; Triawanti, Triawanti (Berkala Kedokteran, 2015)
Orthostatic hypotension is a common problem in the elderly. High incidence of orthostatic hypotension in elderly associated with decreased baroreceptor sensitivity and declining elasticity and muscle strength inferior. This study aims to determine the differences in reaction time in the elderly with and without orthostatic hypotension in Panti Sosial Tresna Werdha âBudi Sejahteraâ Banjarbaru and Martapura. This study was an observational study with cross sectional analytical and decision-purposive sampling technique. Data will be tested for normality prior to the Kolmogorov-Smirnov test for normality. Data analysis using unpaired t test. The results of the study the average reaction time of 30 elderly people with orthostatic hypotension is 2.069 seconds and 30 elderly people without orthostatic hypotension is 1.775 seconds. The results of the Kolmogorov-Smirnov normality test p =0.919 indicates the data are normally. The results of the analysis of the unpaired t test p =0.022 (p <0.05) indicate that there are significant differences. The results that the reaction time in the elderly with orthostatic hypotension longer than without orthostatic hypotension in Panti Sosial Tresna Werdha âBudi Sejahteraâ Banjarbaru and Martapura.Â Keywords: orthostatic hypotension, the elderly, reaction time